Course Distribution System for Bachelors in Information Technology - Hajakamal, Nurhidayatul Husna; Mohamed Din, Aniza (Multidisciplinary Applied Research and Innovation, 2023)
The Course Distribution System for Bachelors in Information Technology (CDSBIT) is a web-based system designed to help the head of the department obtain a list of open slots for each course in an efficient and organized manner. As a timetable must be generated for every semester, the university’s academic affairs office needs to be informed of the number of classes to be opened for each course. Usually, the number of classes for each subject can be determined by dividing the number of students enrolled in the course with the number of students allocated for the course. Due to the large number of courses available each semester, this is not an easy task. The current course distribution process relies heavily on Microsoft Excel. The head of department calculates the number of classes by entering the number of students and choosing the correct formula to perform the calculation. Switching between computers will also make it difficult to keep track of the latest files. Hence, a course distribution system is proposed to facilitate the task of distributing the classes quickly and efficiently. This system aims to assist the head of the department in providing reports and storing data in the database for future review. By using this system, the format will be standardized no matter where it is used. A waterfall model was used as the methodology for this project, which took four months to complete. The system was tested and evaluated based on user acceptance and ease of use by the head of department, deputy dean, and program coordinator in the School of Computing. It can be concluded that CDSBIT can meet the department head's requirements, implying that it can generate reports and obtain a list of slots efficiently.